Dynamic behaviour of honeycombs under mixed shear-compression loading: Experiments and analysis of combined effects of loading angle and cells in-plane orientation. (February 2016) - Tounsi, R.; Markiewicz, E.; Haugou, G.; Chaari, F.; Zouari, B.
Highlights: Honeycomb behaviour is investigated under mixed shear-compression dynamic loading. An improvement of an existing loading device is proposed. An original measurement technique allows to overcome a separation phenomenon. The combined effects of the in-plane orientation and loading angles are analysed. Investigation of collapse mechanisms highlights three deforming pattern modes. Abstract: Cellular materials such as aluminium honeycombs combine lightweight challenges with high mechanical performance for crash energy absorption regulations. This paper investigates experimentally the dynamic behaviour of an aluminium alloy honeycomb under mixed shear-compression loading with a special attention on the combined effects between the cells in-plane orientation and the loading angles. An improvement of an existing experimental SHPB set-up is proposed and an original measurement technique based on an electro optical extensometer is used to overcome a separation phenomenon observed during the test. A significant effect of the loading angle ψ is reported in the crushing responses. The in-plane orientation angle β effects become more significant when the loading angle increases. An investigation of collapse mechanisms is also presented. Three deforming pattern modes are identified and it is shown that their distribution is related to the combined effects of the in-plane orientation angle β and the loading angle ψ .